Evaluation of the Non-Cash Food Assistance Distribution Program in Toari Village, Kolaka Regency - Djabbar, Isra (IJBLE Scientific Publications Community Inc., 2023)
This study aims to determine the process of evaluating the Non-Cash Food Assistance Distribution Program in Toari Village, Toari Sub-district, Kolaka Regency. The BPNT Program aims to reduce the burden of KPM expenditure by fulfilling some of the food needs and providing food with balanced nutrition to KPM. This research uses descriptive research methods with a qualitative approach. The data used in this study consisted of secondary data and primary data sourced from 12 informants. Data collection techniques are interviews and documentation. The qualitative data analysis technique uses data reduction, data display (presentation), and conclusion drawing. The results showed that the BPNT program was ineffective because the unscheduled recipient schedule and KPM did not meet the criteria. In terms of equity, this program has not been evenly distributed to people experiencing poverty because the recipient data is still rarely evaluated, and the BPNT program needs to be right on target. So far, some people are still classified as poor but do not receive assistance.